Жестова поведінка персонажів у романі Люко Дашвар «Село не люди» - Барбара, Наталія; Barbara, Nataliya (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розглянуто жестову (кінетичну) поведінку персонажів твору Люко Дашвар «Село не люди». Тілесну характеристику дійових осіб (жести, міміка, рухи тіла) проаналізовано як засіб творення образів, а також як складник особливої кінематографічності прози письменниці, загалом – феномену успішності книги. In this article gesture (cinetic) behavior of characters in «Село не люди» by Luko Dashvar is described. Body characteristics of people is analysed as the way to create figures, implementation of intentions of the author in artisric area of the text, and also as a bundle of cinematographistic prose of the author, finally – as the phenomenon of the books success. For the implementation of the gesture behavior of characters Luko Dashvar uses her own gestures, mimics, body movement and cinetic demonstration of the informationaly important emotion state (analysis is made based on the example of Darinaʼs personality). Both individual cinemes and describing terms(indirect speech, authorʼs descriptions, remarks) are used as language tools of creating cinetic complexes. Recreation, reproduction of non-verbal behavior, analitycal appointment to the gesture behavior are all ways to convey the gesture behavior.
Gesture Behavior of Characters in the Novel «Село не люди» by Luko Dashvar
Keywords: жестова поведінка; невербальні компоненти комунікації; кінематографічність; кінеми; gesture behavior; сіnematography of prose; non-verbal components of communivation